Novel Insights and Current Evidence for Mechanisms of Atherosclerosis: Mitochondrial Dynamics as a Potential Therapeutic Target - Li, Dan; Yang, Shengjie; Xing, Yanwei; Pan, Limin; Zhao, Ran; Zhao, Yixi; Liu, Longtao; Wu, Min (Frontiers in Cell and Developmental Biology, 2021)
Cardiovascular disease (CVD) is the leading cause of death in the world, and atherosclerosis is the main underlying pathology of CVD. Lipid deposition, oxidative stress, inflammation and endothelial injury are the main causes of atherosclerotic plaques. Obesity, diabetes, hypertension and smoking are risk factors that aggravate the progression of cardiovascular diseases. In recent years, more and more evidences show that abnormal mitochondrial function may be an important cause of atherosclerosis. Mitochondrial fusion and division is an important basis for maintaining its homeostasis and functional realization. Mitochondrial dynamics may be a new target for atherosclerosis therapy, however, the specific mechanism remains unclear. This article provides a detailed overview of the current research in this area of study.